Association Between Syndecan-1, Fluid Overload, and Progressive Acute Kidney Injury After Adult Cardiac Surgery - Xu, Jiarui; Jiang, Wuhua; Li, Yang; Li, Haoxuan; Geng, Xuemei; Chen, Xin; Hu, Jiachang; Shen, Bo; Wang, Yimei; Fang, Yi; Wang, Chunsheng; Luo, Zhe; et al. (Frontiers in Medicine, 2021)
Background Acute kidney injury (AKI) is a common complication after cardiac surgery and the prognosis worsens with the increase in AKI severity. Syndecan-1(SDC-1) is a biomarker of endothelial glycocalyx degradation. Fluid overload (FO) is associated with poor outcomes in AKI patients and may be related to the damage of endothelial function. This study aimed at demonstrating the association between elevated SDC-1, FO, and AKI progression. Methods In this prospective study, we screened patients who underwent cardiac surgery and enrolled patients who experienced an AKI within 48 h after surgery from December 1, 2018 to January 31, 2019. Blood and urine samples were collected at the time of AKI diagnosis for plasma SDC-1 (pSDC-1) and urine SDC-1 (uSDC-1) measurements. Fluid balance (FB) = accumulated (fluid intake (L) - fluid output (L))/body weight (kg) × 100%. FO was defined as FB > 5%. The primary endpoint was progressive AKI, defined as AKI progression from a lower to a higher stage. The patients were divided into progressive AKI group vs. non- progressive AKI group. Results The quartiles of pSDC-1 concentration (117.3[67.4, 242.3] ng/mL) showed a graded association with the incidence of progressive AKI, ranging from 5.0%, 11.9%, 32.6% to 52.4% (p for trend < 0.001). Multivariate logistic regression showed that increased pSDC-1 was an independent risk factor for progressive AKI. The AUC-ROC area of pSDC-1 in predicting AKI progression was 0.847. Linear regression showed a positive correlation between FB and pSDC-1 concentration (R2 = 0.384, p < 0.001). In patients with FO, the progressive AKI incidence was significantly higher in the high pSDC-1 (≥117.3 ng/mL) subgroup than in the low pSDC-1 subgroup (58.3% vs. 17.6%, OR = 9.167, P = 0.005). In patients without FO, the progressive AKI incidence was also significantly higher in the high pSDC-1 subgroup with a lower odds ratio (30.4% vs. 7.4%, OR = 6.714, P = 0.002). Conclusion Elevated pSDC-1 concentration was associated with progressive AKI after cardiac surgery and showed good predictive ability for progressive AKI. FB was related to the increase of pSDC-1. The interaction between pSDC-1 and FB may further aggravate the progression of AKI.